Determinants of the quality of life among pre-elderly and elderly population - Jasrida Yunita; Nurlisis Nurlisis; Wulan Sari (Intelektual Pustaka Media Utama, 2019)
Health problems will appear along with the increasing aging of someone that can reduce the quality of life. Many factors can decreases in quality of life. The purpose of this study was to find the determinants of the quality of life to the pre-elderly and elderly population in the working area of Harapan Raya public health center Pekanbaru, Riau, Indonesia. The design of the research was cross sectional in the pre-elderly population (45–59 years) and the elderly population (60 years and above). There were 103 respondents participated in this study gathared with consecutive sampling techniques. Quality of life was measured using WHOQOL SF-36 questionnaire. Independent variables were body mass index, physical activity, chronic disease, smoking behavior, employment status, residence status, marital status, education, age, and sex. Data were analyzed by univariate, bivariate with Chi square test, and multivariate with multiple logistic regression. The proportion of subjects with low quality of life was 18.4%. Variables related to bivariate were body mass index, smoking behavior, chronic disease, employment status, and sex. Chronic disease (OR=5.5; 95% CI=1.173–25.674) significantly affected the quality of life after being controlled by sex. The quality of life could be explained by this factor about 17%. It is necessary to manage chronic diseases in the public health center and provide information to the pre-elderly and the elderly through counseling, print and electronic media.